From clinical trials to informing clinical decision-making: a review of patient-reported outcomes in nononcology medicines approved by the European Medicines Agency (2018–2022) - Sauchelli, Sarah; Levy, Courtney; Gnanasakthy, Ari; Dave, Vaidehi; Doward, Lynda; Fitzgerald, Kristina A.; Carson, Robyn (Frontiers in Pharmacology, 2025)
IntroductionInformation about a medicine published in the Summary of Product Characteristics (SmPC) and the product’s package leaflet by the European Medicines Agency (EMA) is key to communicate its value to prescribers and patients. The aim of this study was to examine the inclusion of statements related to patient-reported outcomes (PROs) in these documents to communicate patients’ perspectives and experiences of new nononcology medicines.MethodsNononcology therapeutic indications recommended for approval by the EMA between 2018–2022 were identified. The Public Assessment Report(s) (PAR), SmPC, and package leaflet published for each indication were examined. Information about the indication and characteristics relating to how the PROs were assessed in confirmatory studies was extracted.ResultsMost nononcology therapeutic indications (n = 98/140, 70%) contained PRO trial data but less than 50% (n = 64/140, 46%) had PRO-related statements in the SmPC and/or package leaflet. Most statements described treatment benefit (n = 60/64, 94%). Statements were most likely to be included in the SmPC and/or package leaflet if supported by at least 1 randomized controlled trial (n = 52/71, 73%), the endpoint assessed patient-reported symptoms or symptom burden (n = 56/71, 79%), and/or the PRO(s) were assessed as a primary endpoint (n = 24/24, 100%).DiscussionAlthough trial data pertaining to PROs are reviewed when evaluating nononcology drugs, shortfalls persist in the inclusion of PROs when describing treatment benefit in critical documents used to inform treatment decision-making.